Enhanced surface hardening of hydrated concrete composite by strontium nitrate (Sr(NO3)2) aqueous solution. (August 2021) - Cho, Byoung Hooi; Nam, Boo Hyun; Santra, Swadeshmukul; Barry, Mike; Novak, Steve
Abstract: This study experimentally investigates the effects of strontium nitrate (Sr(NO3 )2 ) aqueous solution on hardened concrete composite as a surface hardening method. Density, void content, water sorptivity, and surface abrasion resistance of the concrete mixture treated by Sr(NO3 )2 solution were measured under diverse curing and treatment scenarios. The results showed that 30% Sr(NO3 )2 aqueous solution increases the density by 1.0% and 2.2% and also decreases the void content by 7.4% and 14.4% with the water-cement ratio (w/c) of 0.5 and 0.4, respectively. Water sorptivity of the treated hardened concrete was decreased by 26.4% and 34.0% from the lithium silicate and sodium silicate treatments, respectively. In addition, the Sr(NO3 )2 treatment increases the surface abrasion by 45% from the control specimen and about 25–30% from the two silicate-based treatments. X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive spectrometer (EDS), and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) were conducted to investigate the micro-morphologies, microstructure, and elemental characteristics. The results illustrate that (1) microstructures of hydrated cement matrix are densified, (2) portlandite (CH) in the matrix decreases as time elapses, (3) multiple types of hydrated aluminosilicate minerals (i.e. zeolites) are formulated, and (4) more subsequent polymerization related to C–S–H/C-A-S-H occurs. Lastly, the densifying and strengthening mechanisms of the hydrated cement by the Sr(NO3 )2 treatment process are presented and discussed. Highlights: Treatment process using Sr(NO3 )2 aqueous solution makes a hardened concrete denser. The Sr(NO3 )2 treatment quickly enhances surface abrasion resistance performance of hardened concrete. The Sr(NO3 )2 treatment process may generate diverse types of zeolite in the hydrated cement matrix.